Social demographic factors that influence transformational leadership styles among top management in selected organization in Malaysia - Mohammed, Kabeer Abdullahi; Othman, Jamilah; D'Silva, Jeffrey Lawrence (Canadian Center of Science and Education, 2012)
Literatures have not adequately discusses the influence of demographic variables on Leadership styles among top management in Malaysian organizations. Hence, the overall aim of the study was to investigate if there is significant difference between social demographic factors and transformational leadership style among top management in selected organizations in Malaysia. Data was collected through an instrument of leadership styles known as the MLQ to test the dependent variable (Transformational leadership). The independent variables in this study comprises of gender, race, marital status and educational level. The result of the independent samples t-test and ANOVA revealed that there is no significant difference between social demographic factors and transformational leadership styles. The study concludes that transformational leadership styles do not depends on social demographic factors.